Litter decomposition in Mediterranean ecosystems: Modelling the controlling role of climatic conditions and litter quality (Applied Soil Ecology, 2011)
A new process-based model of litter decomposition, characterized by detailed climatic data input and simple litter quality parameters, is proposed. Compared to existing litter carbon models, speciﬁc implementations for temperature and moisture limiting effects have been adopted. The model is capable to represent decomposition processes in Mediterranean ecosystems, with summer drought slowing down, even at optimal temperatures, the litter decay rates of sclerophyll plants whose leaf masses are rich in structural compounds and low in N content. The model was calibrated by a best ﬁtting procedure of two different datasets. First, unpublished results of litterbag experiments on leaf litter of 9 Mediterranean species, decomposing under controlled and not limiting temperature and water conditions, have been used to estimate the decay rate dependency from litter quality that was deﬁned by only three initial C pools (labile, stable and recalcitrant compounds) instead of traditional N-based indices. Second, a set of published data from three medium-term ﬁeld experiments on a single species, Phillyrea angustifolia, decomposing under different climatic conditions, have been used to estimate the limiting effects of temperature and moisture. The model was then validated against published data on seven other species and showed a correct reproduction ofthemajor patterns of littermass loss during decomposition processes of other seven different Mediterranean species. The model simulations, satisfactory for different litter types under a wide range of climatic conditions, suggest that factors which were not taken into account, such as initial litter N contents, microclimatic variations related to stand structure, soil chemistry and texture, and microbial communities, are not very signiﬁcant for assessing decomposition dynamics in Mediterranean ecosystems. The minimal requirements of input data, the simple structure, and the easiness of parameterisation make our model, among the many other available litter carbon models, an attractive alternative for different research purposes, at least for Mediterranean ecosystems.

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).